2016
DOI: 10.1016/j.bbadis.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

CYP4F2 affects phenotypic outcome in adrenoleukodystrophy by modulating the clearance of very long-chain fatty acids

Abstract: X-linked adrenoleukodystrophy (ALD) is a severe neurodegenerative disorder caused by the accumulation of very long-chain fatty acids (VLCFA) due to mutations in the ABCD1 gene. The phenotypic spectrum ranges from a fatal cerebral demyelinating disease in childhood (cerebral ALD) to a progressive myelopathy without cerebral involvement in adulthood (adrenomyeloneuropathy). Because ABCD1 mutations have no predictive value with respect to clinical outcome a role for modifier genes was postulated. We report that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…There is considerable interest in finding genes that modify the phenotype of ALD. A polymorphism in CYP4F2, the gene that is responsible for peroxisomal ω‐oxidation of VLCFA to very long‐chain dicarboxylic acids was found to increase the risk of development of childhood onset CALD by decreasing the clearance of VLCFA through ω‐oxidation (van Engen et al, ). Eleven microRNAs were identified that had different expression for CALD and AMN and one of them, MiR‐196a, was found to inhibit the expression of two inflammatory signaling factors as well as ELOVL1 (Shah & Singh, ).…”
Section: Cell‐ and Tissue‐specific Pathologymentioning
confidence: 99%
“…There is considerable interest in finding genes that modify the phenotype of ALD. A polymorphism in CYP4F2, the gene that is responsible for peroxisomal ω‐oxidation of VLCFA to very long‐chain dicarboxylic acids was found to increase the risk of development of childhood onset CALD by decreasing the clearance of VLCFA through ω‐oxidation (van Engen et al, ). Eleven microRNAs were identified that had different expression for CALD and AMN and one of them, MiR‐196a, was found to inhibit the expression of two inflammatory signaling factors as well as ELOVL1 (Shah & Singh, ).…”
Section: Cell‐ and Tissue‐specific Pathologymentioning
confidence: 99%
“…In the present study, we first reported that LO has remarkable effects on the hepatic gene expression involved in peroxisomal fatty acid b-oxidation and microsomal fatty acid elongation. More recently, van Engen et al showed that mutation of Cyp4f2 decreases the conversion of VLCFA into very long chain dicarboxylic acids by o-oxidation (van Engen et al 2016). As the o-oxidation is a potential escape route for the deficient peroxisomal VLCFA b-oxidation in ALD, it is interesting whether LO induces expression of Cyp4f2 gene.…”
Section: Changes In Hepatic Gene Expression In Lo-treated Micementioning
confidence: 99%
“…We first focused on alleles which emerged from previous modifier studies to see if they are confirmed. Proposed modifier alleles from target gene studies have identified two candidates within ELOVL1 (rs839765) and CYP4F2 (rs2108622) (Kemp et al, 2012;van Engen et al, 2016). Within this cohort, those modifier alleles do not segregate with ALD phenotype (Table 1), nor are the genotypes shared or lacking in the confidently phenotyped CALD patients.…”
Section: Discordant Genotype Analysis For the Identification Of A Modmentioning
confidence: 94%